Effect of local zoledronate on implant osseointegration in a rat model - Back, David A.; Schmidmaier, Gerhard (BMC musculoskeletal disorders, 2012)
An implant coating with poly(D, L-lactide) (PDLLA) releasing incorporated Zoledronic acid (ZOL) has already proven to positively effect osteoblasts, to inhibit osteoclasts and to accelerate fracture healing. Aim of this study was to investigate the release kinetics of the chosen coating and the effect of different concentrations of ZOL locally released from this coating on the osseointegration of implants.
Published: 22 March 2012
Gesehen am 31.07.2018